Study on Interactive Damping of Primary-Secondary Coupled System - Lihua Zhu; Haoyi Zhou; Jun Dai (Shock and Vibration)
In order to study the interactive damping of a primary-secondary coupled system, three damping strategies are presented. Based on it, three dynamic models were established: the 2-DOF series model, spatial dynamic model, and 3-DOF series model. According to the concept and calculation methods of random vibration, the displacement, velocity, and acceleration variances of each model were derived as response functions of the coupled system. Using MATLAB to analyze the response functions, we studied the manner in which the system response is affected by the frequency and mass ratios of the primary structure and secondary structures, the plane layout of the secondary structure, and the quality, frequency, and damping of the connection structure, respectively. Thereafter, combined with the multiobjective optimization method, optimal parameters were selected to minimize the coupled system response in order to achieve interactive damping.